Time-resolved formation of excited atomic and molecular states in XUV-induced nanoplasmas in ammonia clusters. Issue 15 (5th April 2020) - Michiels, Rupert; LaForge, Aaron C.; Bohlen, Matthias; Callegari, Carlo; Clark, Andrew; von Conta, Aaron; Coreno, Marcello; Di Fraia, Michele; Drabbels, Marcel; Finetti, Paola; Huppert, Martin; Oliver, Veronica; et al.
Abstract : The formation of excited hydrogen in XUV-induced ammonia plasmas was studied in a time-resolved way using an XUV-UV pump–probe scheme. Abstract : High intensity XUV radiation from a free-electron laser (FEL) was used to create a nanoplasma inside ammonia clusters with the intent of studying the resulting electron–ion interactions and their interplay with plasma evolution. In a plasma-like state, electrons with kinetic energy lower than the local collective Coulomb potential of the positive ionic core are trapped in the cluster and take part in secondary processes ( e.g. electron-impact excitation/ionization and electron–ion recombination) which lead to subsequent excited and neutral molecular fragmentation. Using a time-delayed UV laser, the dynamics of the excited atomic and molecular states are probed from −0.1 ps to 18 ps. We identify three different phases of molecular fragmentation that are clearly distinguished by the effect of the probe laser on the ionic and electronic yield. We propose a simple model to rationalize our data and further identify two separate channels leading to the formation of excited hydrogen.